The effect of tongue elevation muscle training in patients with obstructive sleep apnea: A randomised controlled trial. (21st September 2022) - Poncin, William; Correvon, Nils; Tam, Jonathan; Borel, Jean‐Christian; Berger, Mathieu; Liistro, Giuseppe; Mwenge, Benny; Heinzer, Raphael; Contal, Olivier
Abstract: Background: Oropharyngeal myofunctional therapy is a multi‐component therapy effective to reduce the severity of obstructive sleep apnoea (OSA). However, existing protocols are difficult to replicate in the clinical setting. There is a need to isolate the specific effectiveness of each component of the therapy. Objective: To assess the effects of a 6 weeks tongue elevation training programme in patients with OSA. Methods: We conducted a multicentre randomised controlled trial. Eligible participants were adults diagnosed with moderate OSA who presented low adherence to continuous positive airway pressure therapy (mean use <4 h per night). The intervention group completed a 6 weeks tongue elevation training protocol that consisted in anterior tongue elevation strength and endurance tasks with the Iowa Oral Performance Instrument. The control group completed a 6 weeks sham training protocol that involved expiratory muscle training at very low intensity. Polygraphy data, tongue force and endurance, and OSA symptoms were evaluated pre‐ and post‐intervention. The primary outcome was apneoa‐hypopnea index (AHI). Results: Twenty‐seven patients (55 ± 11 years) were recruited. According to modified intention‐to‐treat analysis ( n = 25), changes in AHI and c did not significantly differ between groups. Daytime sleepiness (Epworth Sleepiness Scale) and tongue endurance significantly improved in the intervention group compared to the control group ( p = .015 and .022, respectively). In the intervention group, 75% of participants had a decrease in daytime sleepiness that exceeded the minimal clinically important difference. Conclusion: Six weeks of tongue elevation muscle training had no effect on OSA severity. Abstract : There is a need to elucidate the specific effect of a well‐defined component of orophareyngeal myofunctional therapy for patients with obstructive sleep apnea: tongue elevation muscle training. A 6‐week tongue elevation training programme did not change AHI or other polygraphy‐derived parameters compared to the control group. However, daytime sleepiness and tongue endurance significantly improved in the intervention group compared to the control group.